HUMANIZING ARTIFICIAL INTELLIGENCE THROUGH INFORMATION TECHNOLOGY: ETHICAL PATHWAYS IN EDUCATION AND GOVERNANCE - Wan Abdul Rahim Wan Mohd Isa; Nor Liyana Mohd Shuib (Penerbit UTHM, 2026)
Artificial Intelligence is fundamentally transforming society, yet its rapid ascent raises profound ethical questions regarding human agency. Humanizing Artificial Intelligence through Information Technology explores the critical intersection of AI, IT and human values, specifically within education and public governance. The authors argue that Information Technology serves as the essential infrastructure for embedding ethics into algorithmic systems. By contrasting machine-centered paradigms with a human-centered lens, this book emphasizes fairness, transparency, and accountability. It details how IT frameworks ranging from privacy-by-design to robust audit trails, effectively operationalize these vital principles. Readers will discover strategies for managing algorithmic bias, ensuring data sovereignty, and maintaining meaningful human control. Featuring comprehensive case studies and actionable best practices, this volume offers a strategic roadmap for educators, policymakers and technologist alike. This is an essential guide for building a sustainable, ethical future where AI technology successfully augments human potential and strengthens our diverse democratic institutions and societies globally.